PENGARUH VARIASI DOSIS PUPUK LIMBAH CAIR NANAS (LCN) TERHADAP PERTUMBUHAN DAN KADAR KALSIUM BAYAM MERAH (ALTHERNANTHERA AMOENA VOSS.) UNTUK PENYUSUNAN BAHAN AJAR MONOGRAF BERBASIS SAINTIFIK MATERI PERTUMBUHAN DAN PERKEMBANGAN - Qurniani, Arifah (Lembaga Penelitian UM Metro, 2017)
Spinach is a common vegetable that is popular with the community, calcium content reaches 368mg/100gr. Spinach includes family Amaranthaceae, Amaranthus clan that contains lots of water (herbaceous). The type of research is experimental research, the effect of giving dose variation. The study design was using Completely Randomized Design (RAL). Liquid Fertilizer LCN with several doses of control (0ml), A (150ml), B (200ml), and C (250ml). The result of analysis concludes that there is influence of LCN fertilizer to growth of red spinach, there is influence of LCN fertilizer can increase the calcium content of red spinach plant, there is influence of LCN fertilizer on growth and calcium level, and the result of research can be used as design of monograph based materials scientifically growth material and development.